Analysis and Simulation of Wavelet Carrier Modulation with Clipping Techniques in Mobile WiMAX - Muhamad Mardanu Kusuma; Rina Pudji Astuti; Dharu Arseno (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2015)
The implementation of OFDM results in relatively high peak-to-average power ratio (PAPR) due to IFFT process to generate orthogonal subcarriers. A number of studies have attempted to apply various techniques to minimize PAPR by apllying the Wavelet transform as a substitution for Fourier transform. Another technique used to reduce the PAPR is clipping. In this thesis, the clipping technique was applied on the Wavelet based OFDM in mobile WiMAX standard to obtain better performance. The results indicate that Wavelet based OFDM has better immunity to noise and more resistant to Doppler shift than Fourier based OFDM. Sym 7 with Classical clipping and CR 1.2 can be selected and applied on wavelet-based OFDM in mobile WiMAX.